ASPERGILLOMA PADA TUBERKULOSIS PARU: LITERATURE REVIEW - Arianto, Wily; Lasmaria, Rohani (Media Penelitian dan Pengembangan Kesehatan, 2024)
Indonesia ranking among the top six countries with the highest TB burden. In the aftermath of pulmonary TB, fungal infections, particularly those caused by Aspergillus species, have emerged as a notable complication. The predominant species, Aspergillus fumigatus, is responsible for a spectrum of conditions ranging from invasive to noninvasive aspergillosis. This literature review aims to provide an exhaustive analysis of post-TB pulmonary aspergilloma, a clinical condition characterized by the growth of Aspergillus fungal balls within pre-existing lung cavities. Utilizing databases such as PubMed, Science Direct, EBSCO, Emerald, Scopus, and Google Scholar, and employing keywords such as "tuberculosis," "aspergillus," "aspergilloma," and "pulmonary," we meticulously applied the PICO framework and the CRAAP (Currency, Relevance, Authority, Accuracy, and Purpose) criteria to select 20 pertinent articles. The findings indicate that pulmonary aspergilloma manifests in approximately 11% to 17% of individuals post-TB treatment, presenting a clinical spectrum from asymptomatic to severe, life-threatening hemoptysis. Classification into simple and complex aspergilloma is based on specific clinical and radiological criteria. Diagnosis is contingent upon the identification of clinical symptoms, assessment of risk factors, and the corroboration of Aspergillus infection through radiological (chest X-ray and CT scan) and serological or microbiological evidence. Management of pulmonary aspergilloma entails non-operative and operative strategies, with surgical intervention being the definitive treatment, especially in cases of recurrent or massive hemoptysis. The review underscores the persistent challenge of TB in Indonesia, exacerbated by secondary fungal infections such as aspergillosis among pulmonary TB survivors. Aspergillus fumigatus is identified as the primary fungal pathogen, leading to pulmonary aspergilloma.